Electro‐optic filter based on guided‐mode resonance for optical communication. Issue 23 (1st November 2018) - Ren, Zhibin; Sun, Yahui; Hu, Jiasheng; Zhang, Shuqing; Lin, Zihao; Zhi, Xiyang
Abstract : An electro‐optic filter based on guided‐mode resonance for optical communication has been designed and fabricated. The rigorous coupled‐wave analysis is used to calculate the reflection spectra of the designed filter. The grating structure of the filter is patterned by interference lithography with two ultraviolet laser beams. The polymer‐dispersed liquid crystal is injected into the gap between the glass substrate and the bottom of the grating to fabricate the electro‐optic filter. The measured spectra of the fabricated filter exhibit a 38.7 nm shift of the resonant reflected wavelength by controlling the applied voltage.